Peranan Pihak Imigrasi Dalam Mengawasi Pintu Masuk dan Keluar Negara Indonesia - Kenneth Nicolaus Yoseph; Devina Yuka Utami; Budy Mulyawan (Peneliti.net, 2022)
This research is motivated by the main problem related to the supervision of the Indonesian immigration authorities which is inadequate when compared to immigration control with other countries. In many cases, Indonesian immigration authorities often fail to face immigration violations committed by foreign nationals, therefore improvements in supervision by Indonesian immigration authorities need to be carried out to minimize the negative impact of immigration violations committed by foreign nationals. The results of this study found immigration problems that should have been fixed by collaborating with other agencies, one of which was the navy or improving the system or internal rules of the Directorate General of Immigration itself so that the optimization of supervision related to entrances and exits can run as expected.